Repetitive Transcranial Magnetic Stimulation of the Brain: Mechanisms from Animal and Experimental Models. (February 2017) - Tang, Alexander; Thickbroom, Gary; Rodger, Jennifer
Since the development of transcranial magnetic stimulation (TMS) in the early 1980s, a range of repetitive TMS (rTMS) protocols are now available to modulate neuronal plasticity in clinical and non-clinical populations. However, despite the wide application of rTMS in humans, the mechanisms underlying rTMS-induced plasticity remain uncertain. Animal and in vitro models provide an adjunct method of investigating potential synaptic and non-synaptic mechanisms of rTMS-induced plasticity. This review summarizes in vitro experimental studies, in vivo studies with intact rodents, and preclinical models of selected neurological disorders—Parkinson's disease, depression, and stroke. We suggest that these basic research findings can contribute to the understanding of how rTMS-induced plasticity can be modulated, including novel mechanisms such as neuroprotection and neurogenesis that have significant therapeutic potential.